Aree Lkhua Song: a musicological analysis of Pakapel tradition among the Kelabit Tribe in the Upper Baram river, Sarawak - Mohd Hassan Abdullah (Tanjong Malim, 2020)
Aree Lkhua Song: a musicological analysis of Pakapel tradition among the Kelabit Tribe in the Upper Baram river, Sarawak by Mohd Hassan Abdullah